Worrorra: a language of the north-west Kimberley coast - Clendon, Mark (University of Adelaide Press, 2014)
The Kimberley Arafuran language Worrorra was spoken traditionally on the remote coastline and precipitously beautiful hinterland between the Walcott Inlet and the Prince Regent River. The language described here is that attested by its last full speakers, Patsy Lulpunda, Amy Peters and Daisy Utemorrah. Patsy Lulpunda was a child when Europeans first entered her country in 1912, and Amy Peters and Daisy Utemorrah both grew up on the Kunmunya mission. This comprehensive and detailed grammar provides as well an historical and cultural context for a society now drastically altered. In the 1950s Worrorra people left their traditional land and from the 1970s the number of people speaking Worrorra as their first language declined dramatically. Worrorra is a highly polysynthetic language, characterised by overarching concord and a high degree of morphological fusion. Verbal semantics involve a voicing opposition and an extensive system of evidentiality-marking. Worrorra has elaborate systems of pragmatic reference, a derivational morphology that projects agreement-class concord across most lexical categories and complex predicates that incorporate one verb within another. Nouns are distributed among five genders, the intensional properties of which define dynamic oppositions between men and women on the one hand, and earth and sky on the other. This volume will be of interest to morphologists, syntacticians, semanticists, anthropologists, typologists, and readers interested in Australian language and culture generally.